Insight into the effect of screw dislocations and oxygen vacancy defects on the optical nonlinear refraction response in chemically grown ZnO/Al2O3 films - Agrawal, Arpana; Saroj, Rajendra K.; Dar, Tanveer A.; Baraskar, Priyanka; Sen, Pratima; Dhar, Subhabrata (Journal of applied physics, 2017)
We report the effect of screw dislocations and oxygen vacancy defects on the optical nonlinear refraction response of ZnO films grown on a sapphire substrate at various oxygen flow rates using the chemical vapor deposition technique. The nonlinear refraction response was investigated in the off-resonant regime using a CW He-Ne laser source to examine the role of the intermediate bandgap states. It has been observed that the structural defects strongly influence the optical nonlinearity in the off-resonant regime. Nonlinearity has been found to improve as the oxygen flow rate is lowered from 2 sccm to 0.3 sccm. From photoluminescence studies, we observe that the enhanced defect density of the electronic defect levels due to the increased concentration of structural defects (with the decrease in the oxygen flow rate) is responsible for this improved optical nonlinearity along with the thermal effect. This suggests that defect engineering is an effective way to tailor the nonlinearity of ZnO films and their utility for optoelectronic device applications.